Speed Limit Policies: The Output Gap and Optimal Monetary Policy - Walsh, Carl E (American Economic Review, 2003)
In a standard New Keynesian model, a myopic central bank concerned with stabilizing inflation and changes in the output gap will implement a policy under discretion that replicates the optimal, timeless perspective, precommitment policy. By stabilizing output gap changes, the central bank imparts inertia into output and inflation that is absent under pure discretion. Even a fully optimizing (i.e., non-myopic) central bank operating in a discretionary policy environment achieves better social outcomes if it focuses on inflation and changes in the output gap than are achieved under inflation targeting.(This abstract was borrowed from another version of this item.)